Thermal, Optical Properties and Structural Investigation of Tm3+ doped TeO2-ZnO-TiO2 Glass System - (:unkn) unknown (E D P SCIENCES, 2010)
Tellurite based infrared glasses in the Tm3+ doped TeO2-ZnO-TiO2 system were prepared and its optical properties and crystallization kinetics investigated by using UV-VIS-NIR spectrophometer and differential thermal analysis method (DTA). All the glasses were transparent from visible to near infrared region for different ZnO glass compositions (x = 5, 10, 20, and 30 mol%). In the experiments, optical energy band gaps and Urbach energies were estimated from the optical absorption spectra between 300 and 800 nm wavelength region. The spectroscopic properties including absorption spectra and absorption cross sections of Tm3+ doped TeO2-ZnO-TiO2 were measured and calculated. In addition, glass transition (T-g), crystallization (T-p) and melting temperature (T-m) were determined by using the DTA plots. Crystallization activation energies and crystallization mechanism were determined from the DTA curves measured with different heating rates (20, 30, and 40 degrees C/min). Finally, DTA results obtained with a heating rate of 20 degrees C/min show that the peak crystallization temperature increases from 463 to 533 degrees C as the ZnO content increases from 5 to 30 mol%.